The association between diabetes and migraine: a systematic review and meta-analysis - Ramadan, Heba (Headache Medicine, 2024)
Introduction Diabetes and migraine are prevalent conditions that can significantly impact quality of life. Existing review suggests a possible connection between the two, though findings have varied. Objective This review aims to assess the prevalence and association between diabetes and migraine through a meta-analysis. Methods This approach was applied through searches in Scopus, WOS, PubMed, and Google Scholar. A PRISMA checklist was followed. The quality assessment was checked. The included studies investigated either migraine in diabetes patients or diabetes in migraine patients, with no restriction on age groups or timeframes. The meta-analyses were performed using Jamovi 2.3.28 and SPSS Version 28. Results Two groups of studies were analyzed. Group 1 (n= 8) assessed migraine prevalence in patients with diabetes. The overall migraine prevalence was 12% (95% CI: 6%- 17%). Type 2 diabetes had a migraine prevalence of 8% (95% CI: 1%- 15%), significantly affected by study demographics and duration of diabetes. Type 1 diabetes showed a lower migraine prevalence (1%). Odds ratios indicated a non- significant decrease in migraine prevalence among diabetes patients overall and a significant decrease for type 1 diabetes. Group 2 (n= 17) examined diabetes prevalence among migraine patients. The overall odds ratio for diabetes prevalence was 0.86 (p< 0.05), indicating a significant decrease. Specific analyses showed a nearly significant reduction in diabetes prevalence for migraine with aura (OR= 0.78, p = 0.05) and no significant difference for migraine without aura (OR≈ 1, p = 0.95). Conclusions The results suggest a generally lower prevalence of migraine among diabetes patients, particularly with type 1 diabetes, while diabetes prevalence is lower among migraine patients, especially those with aura.